Hocazâde Süleyman Şevket’in Gözünden Lozan Sonrası Kıbrıs Türkleri / Cyprus Turks After Lausanne Through the Eyes of Hocazâde Süleyman Şevket - Şahin, Cemile (Journal of History Culture and Art Research, 2019)
Abstract After Turkey had approved formally that Cyprus was under the British rule with the Treaty of Lausanne, some of the Turkish Cypriot population that were accepted as Turkish citizens stayed in the island through British nationality, many Turkish Cypriots had to leave the island but in the later period, the challenges that the Turkish Cypriots experienced continued to increase. When compared with the Greek Cypriots, the challenges that the Turkish Cypriots who were quite backward in political, social and economic terms had were ignorance, poverty, non-organizing problem, and migration. Hocazade Süleyman Şevket, who was among the intellectuals trying to find valid solutions by examining the situation of the Turkish Cypriots, wrote articles about the situation of the Turkish Cypriots in the newspaper, Soz, one of the important newspapers of Cyprus. Süleyman Şevket frequently expressed his anxiety about the future of Turkish Cypriots and he also stated issues such as the inability to unity, ignorance, and poverty that were common among Turks dragged them into disaster and emphasized that these issues could be resolved only by modeling the Turkish Republic and the reform movements. In this study, the issues that the Turkish Cypriots had in education, culture and social life in the post-Lausanne period are discussed based on the article “How are the Turkish Cypriots?” by Süleyman Şevket. In addition, archival documents and other related reports of this period are examined comparatively. Öz Lozan Antlaşması’yla Kıbrıs’ın İngiliz yönetimine geçtiğinin Türkiye tarafından resmen onaylanması üzerine, o güne kadar Türk tebaası olarak kabul edilen Kıbrıslı Türklerden bir kısmı İngiliz uyruğuna geçerek adada kalırken, çok sayıda Kıbrıslı Türk de adadan göç etmek zorunda kalmış, ancak bundan sonraki süreçte, Kıbrıs Türkleri için yaşanan sıkıntılar artarak devam etmiştir. Kıbrıs Rumları ile mukayese edildiğinde; siyasal, toplumsal ve iktisadi bakımdan oldukça geri oldukları gözlenen Kıbrıs Türklerinin yaşadıkların sorunların başında, cehalet, yoksulluk, örgütlenememe sorunu ve göç yer almıştır. Kıbrıs Türklerinin içinde bulundukları durumu inceleyerek, geçerli çözüm yolları bulmaya çalışan aydınlar arasında bulunan Hocazade Süleyman Şevket, Kıbrıs’ın önemli gazetelerinden olan Söz gazetesinde, Kıbrıs Türklerinin durumu ile ilgili yazılar kaleme almıştır. Süleyman Şevket, Kıbrıs Türklerinin geleceğinden duyduğu endişeyi sıklıkla dile getirmiş olup, Türkler arasında yaygın olan; birlik olamama, cehalet ve fakirliğin, onları her geçen gün felakete sürüklemekte olduğunu, bu sorunların, Türkiye Cumhuriyeti ve inkılap hareketlerinin örnek alınarak çözülebileceğini ifade etmiştir. Bu çalışmada, Süleyman Şevket’in, “Kıbrıs Türkleri Ne Halde?” başlıklı yazısından yola çıkılarak, Lozan sonrası dönemde Kıbrıs Türklerinin eğitim, kültür, ekonomik ve sosyal hayatta yaşadıkları sıkıntılar ele alınmıştır. Ayrıca, bu döneme ait arşiv belgeleri ve konu ile ilgili diğer raporlar da mukayeseli olarak incelenmiştir.